'You can settle here': immobility aspirations and capabilities among youth from rural Honduras. Issue 1 (2nd January 2023) - Wyngaarden, Sara; Humphries, Sally; Skinner, Kelly; Lobo Tosta, Esmeralda; Zelaya Portillo, Veronica; Orellana, Paola; Dodd, Warren
ABSTRACT: A 'mobility bias' has been identified in the migration literature, whereby researchers have focused on the drivers of migration while neglecting factors that influence immobility decisions. Addressing this gap is important for developing a holistic understanding of human mobility patterns and effectively mitigating experiences of distress migration among populations experiencing marginalisation. This qualitative study explored (im)mobility aspirations and decisions among youth from two rural municipalities of Honduras. Thirty-two in-depth semi-structured interviews were conducted in 2019. Analyses were guided by the aspiration-capabilities framework. Findings revealed retain and repel factors shaping immobility aspirations among rural youth. Respondents who were practicing immobility also identified the capacity to envision viable rural livelihood options as an important precursor to actualising their immobility preferences. They described creatively applying skills, leveraging resources, and engaging with enabling institutions in order to turn immobility aspirations into capabilities. They contested scarcity narratives driving outmigration among their peers and positioned themselves as active agents of their immobility decisions, claiming dignity in their livelihood choices. These findings enrich an understanding of immobility as an agentic livelihood choice in a context with high rates of outmigration, making both empirical and theoretical contributions to the (im)mobility literature.